Personal Values and Substance Use in Adolescence and Young Adulthood: Risk or Protective Factors?. (28th January 2023) - Danioni, Francesca; Villani, Daniela; Ranieri, Sonia
Abstract: Background : Personal values are desirable trans-situational goals that serve as guiding principles in people's lives and have been widely found to be related to people's behavior. Objectives : This study aimed at investigating the relation between personal values and youth involvement in frequency of alcohol and cannabis use and problems related to substance use, comparing two groups of adolescents and young adults: 237 adolescents (age 14–19 years; 58.2% females) and 236 young adults (age 20–30 years; 78.8% females). Participants were asked to fill in an online self-report questionnaire aimed at assessing the constructs of interest. Results : The results showed that openness to change, despite being more prioritized by adolescents, was significantly positively related to frequency of cannabis use and problems related to substance use only for young adults. Conclusions : Implications for preventive interventions and further expansions of the study are discussed.